Polyphiloprogenitive: T.S.Eliot - Brlek, Tomislav (Array, 2002)
In the contested and mutually defining contexts of institutionalisation of modernism, post-modernism and the avant-garde, the case of T.S.Eliot might perhaps be seen as symptomatic of the mechanisms of critical taming, interpretative appropriation and academic dissemination.